2020
DOI: 10.1038/s41598-020-70177-w
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the chemical space of fungal polyketides by phylogeny-based bioinformatics analysis of polyketide synthase-nonribosomal peptide synthetase and its modification enzymes

Abstract: Fungal polyketide synthase (PKS)–nonribosomal peptide synthetase (NRPS) hybrids are key enzymes for synthesizing structurally diverse hybrid natural products (NPs) with characteristic biological activities. Predicting their chemical space is of particular importance in the field of natural product chemistry. However, the unexplored programming rule of the PKS module has prevented prediction of its chemical structure based on amino acid sequences. Here, we conducted a phylogenetic analysis of 884 PKS–NRPS hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 55 publications
(86 reference statements)
0
26
1
Order By: Relevance
“…α,β‐Hydrolases related to PyiE and ORFZ are commonly found encoded in fungal PKS‐NRPS biosynthetic gene clusters, especially those with a reductive release mechanism [17] . For example, the cytochalasin E (CcsE), [5a] fusarin (Fus2), [18a, 24] pseurotin (PsoG), [18c] and phomacin (SnoG) [25] gene clusters all encode homologous α,β‐hydrolases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…α,β‐Hydrolases related to PyiE and ORFZ are commonly found encoded in fungal PKS‐NRPS biosynthetic gene clusters, especially those with a reductive release mechanism [17] . For example, the cytochalasin E (CcsE), [5a] fusarin (Fus2), [18a, 24] pseurotin (PsoG), [18c] and phomacin (SnoG) [25] gene clusters all encode homologous α,β‐hydrolases.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrolytic enzymes similar to PyiE, and its ACE1 homolog ORFZ, are encoded in the BGC of all known cytochalasans, [17] as well as in other BGC which encode the biosynthesis of compounds such as fusarin C where the PKS‐NRPS has a reductive release mechanism [18] . However, the precise function of these hydrolytic enzymes remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that substrates bind to the pocket in a similar way (tetramic acid-front and polyene-back orientation) and stereoselective [4+2] cycloadditions proceed. Recent phylogenetic analysis has suggested that approximately 100 sequences are potentially involved in DP biosynthesis 40 . Therefore, this group of enzymes widely found in Ascomycota fungi would be an attractive target for structure-function relationship studies, providing key structural features to determine the stereoselectivity of these reactions.…”
Section: Discussionmentioning
confidence: 99%
“…1b) and even an unidentified metabolite (2 S ,3 R ,8 R ,11 S ). Recent phylogenetic analysis suggested that approximately 100 sequences are potentially involved in DP biosynthesis 49 . Therefore, this group of enzymes, which is widespread in Ascomycota fungi, are attractive targets for structure–function relationship studies, providing key structural features for determining the stereoselectivity of these reactions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, vehicle degradation may sustain or control a gradual delivery of the peptide at the right site [ 65 , 66 , 67 , 68 ]. A greater decrease in the number of peptides entering the pipeline for peptide development is achieved by in silico selection of new and improved prediction tools for candidate selection based on an expected higher effectiveness or decreased toxicity [ 69 , 70 , 71 , 72 , 73 ].…”
Section: Introductionmentioning
confidence: 99%